2021
DOI: 10.1093/mnras/stab3313
|View full text |Cite
|
Sign up to set email alerts
|

A new method for measuring the 3D turbulent velocity dispersion of molecular clouds

Abstract: The structure and star formation activity of a molecular cloud are fundamentally linked to its internal turbulence. However, accurately measuring the turbulent velocity dispersion is challenging due to projection effects and observational limitations, such as telescope resolution, particularly for clouds that include non-turbulent motions, such as large-scale rotation. Here, we develop a new method to recover the 3D turbulent velocity dispersion (σv,3D) from position–position–velocity (PPV) data. We simulate a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…On the other hand, simulations have shown that turbulence can also cause small-scale fluctuations on the measured velocity centroids (Stewart & Federrath 2022), which should affect the patterns in our ∇ maps (Fig. 6).…”
Section: Local Velocity Gradientmentioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, simulations have shown that turbulence can also cause small-scale fluctuations on the measured velocity centroids (Stewart & Federrath 2022), which should affect the patterns in our ∇ maps (Fig. 6).…”
Section: Local Velocity Gradientmentioning
confidence: 92%
“…The observed σ nt can also be higher than the intrinsic turbulence velocity dispersion, because the variation of LSR velocity centroids within the beam can partially arise from the ordered motions (e.g., rotation, shear motions) rather than pure turbulence (see also Stewart & Federrath 2022). Making use of the derived local velocity gradients, we could roughly estimate the contributions to the observed σ nt .…”
Section: Widespread Subsonic Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…∇ in the red and blue dashed boxes appear to be dominated by a northeast-southwest velocity gradient which is almost perpendicular to the filament's long axis and the plane-of-the-sky magnetic field. Such transverse velocity gradients can be caused by filament rotation (e.g., Zhang et al 2020;Stewart & Federrath 2022). However, ∇ in the red and blue dashed boxes show opposite directions, ruling out the filament's rigid rotation.…”
Section: Local Velocity Gradientmentioning
confidence: 99%
“…Hence, the dissipation in our turbulence is purely numerical. Because the ion Alfvén velocity fluctuations are dominated by the low-k modes (see Supplementary Figure S2, which shows that the rms statistics converge quickly as the number of grid elements in the simulations increase) the macroscopic diffusion of SCRs ought to be also controlled by the low-k modes (low in the case of observations may either correspond to modes comparable to the scale of the driving source, or the largest modes in the observational region that is being examined, see e.g., Federrath et al, 2016;Stewart and Federrath 2022). This means the exact prescription for dissipation ought not to matter for the ion Alfvén velocity statistics that we describe in this study.…”
Section: Caveats In Our Studymentioning
confidence: 99%